2019
DOI: 10.1136/bmjopen-2018-023625
|View full text |Cite
|
Sign up to set email alerts
|

Dairy product consumption and development of cancer: an overview of reviews

Abstract: ObjectivesTo provide a comprehensive systematic overview of current evidence from pooled analyses/meta-analyses and systematic reviews (PMASRs) pertaining to dairy consumption and incident cancer and/or all-cause or cancer-specific mortality.DesignOverview of reviews.SettingCommunity setting.ParticipantsThe unit of analysis is PMASRs. A total of 42 PMASRs was included in this overview of reviews.Interventions/exposuresAny dairy product consumption (eg, milk, yogurt, etc).Primary and secondary outcomes measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
(64 reference statements)
0
15
0
2
Order By: Relevance
“…The association between saturated fat in dairy products and cancer risk is not clearly established, due to methodologic limitations of most studies [134]. A large U.S. population-based cohort study and meta-analysis found no link between total dairy consumption and risk of cancer or cancer mortality.…”
Section: Saturated Fatmentioning
confidence: 99%
“…The association between saturated fat in dairy products and cancer risk is not clearly established, due to methodologic limitations of most studies [134]. A large U.S. population-based cohort study and meta-analysis found no link between total dairy consumption and risk of cancer or cancer mortality.…”
Section: Saturated Fatmentioning
confidence: 99%
“…It was reported to have antioxidant ( Almasaudi et al, 2016 , Ait Abderrahim et al, 2017 ), anti-inflammatory and estrogenic effects ( Porcza et al, 2016 ), apoptotic, immunomodulatory, antiproliferative ( Jaganathan et al, 2015 ) and anticarcinogenic action ( Subramanian et al, 2016 ). Besides, consumption of milk or dairy products (butter and Yoghurt) is correlated with a reduced risk of numerous types of cancer ( Jeyaraman et al, 2019 ). These properties are attributed to the variety of components such as fat compounds, conjugated linoleic acid, and proteins such as casein and vitamins (A, B, C, D) which have been proved to have protective and/or anticarcinogenic properties ( Davoodi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found a positive association between dairy consumption and PDAC risk [155]. Other studies, some at specific locations, did not find any association [156][157][158][159]. Some early reports linked the kinds of fatty acids found in dairy products to increased cancer risk.…”
Section: Dairymentioning
confidence: 99%